Latinoamérica y la CPI: afrontar la impunidad en Colombia - Bárbara Direito (Araucaria)
In order to understand the degree to which the International Criminal Court (ICC) - the purpose of which is to combat impunity for crimes against humanity committed after 1 July 2002 - we must evaluate how the international community has reacted to it, and the degree to which it is implementing the fundamental principles consecrated by the Rome Statute. The ICC depends on the support of regions to work efficiently. Given that reactions to it have varied from region to region, this can have a serious impact on its effectiveness. This article examines the level of Latin American cooperation with the ICC. Various countries of that region were particularly receptive toward the project of establishing a permanent international criminal court. But the real test of commitment will come when there is an investigation of (and even judicial proceedings against) Latin American nationals, or of and against a situation occurring in a Latin American country. The case of Colombia, a country which has been the stage for innumerable violations of human rights over the past decades and where the conflict is still producing victims, can be a real test case. But we need to know whether all the legal requirements that allow the organs of the Court to act are present, and to evaluate the way in which the ICC could become a large or small part of a strategy to combat impunity for war crimes and crimes against humanity in Colombia.